Synthesis and Characterization of Hybrid Nanomaterials for Biomedical Applications - Jabr, Hussein Fadel; Shyaal, Jassim Qassim; dakhil, Ruaa nadheer; Muhamad, Bozhin Rahim; Abbas, Zahra Osama (American Journal of Biodiversity, 2025)
Nanomaterials are interesting materials and exhibit superior and tunable physical, chemical, and biological properties in comparison with bulk materials. There are many types of nanomaterials that have been created via different processes, that is, chemical, physical, green chemistry, and biological. Based on the properties of a nanoparticle, the desirable functional groups are functionalized with different linkers, polymers, and nanomaterials that are grafted on them or complexed with them. This combination is also referred to as a hybrid nanomaterial. Hybrid nanomaterials can be of a wide range of types, that is, monolithic, fiber, film, membrane, and powder, and can be prepared in a different 2D and 3D architecture. Nanomaterials have many applications, and the spectrum of use is already broader than that of micro-sized materials, and the major part of biotechnological properties is ascribed to nanoscale particles. Hybrid nanomaterials are proven to be drastically different from their bulk and raw materials with respect to their physiochemical features, that is, composition, crystallographic symmetry, morphology, and porosity. When combining nanomaterials, these physiochemical features affect the bioavailability, biocompatibility, pharmacokinetics, and pharmacodynamics of the employed compounds. This further enhances the value-added properties of hybrid nanomaterials. Those properties can be adequately adjusted to make them suitable for a wide variety of applications. However, understanding the relationship between nanomaterial properties and their specific features is hindered by the limited information that can be gained from experimental studies. Hence, classical experimental designs do not allow fully characterizing the interactions between nanomaterials and the properties of resulting nanomaterials. In response to that, hybrid nanomaterials are the topic of study for physicists, chemists, and computational scientists to ensure that they have the highest performance, fine-tuned, and properly developed for possible use in a broad range of technological and biotech sector advancements.